Highly‐Selective Harvesting of (6,4) SWCNTs Using the Aqueous Two‐Phase Extraction Method and Nonionic Surfactants - Blazej Podlesny; Kevin R. Hinkle; Keita Hayashi; Yoshiaki Niidome; Tomohiro Shiraki; Dawid Janas (Advanced Science)
Abstract Monochiral single‐walled carbon nanotubes (SWCNTs) are indispensable for advancing the technology readiness level of nanocarbon‐based concepts. In recent times, many separation techniques have been developed to obtain specific SWCNTs from raw unsorted materials to catalyze the development in this area. This work presents how the aqueous two‐phase extraction (ATPE) method can be enhanced for the straightforward isolation of (6,4) SWCNTs in one step. Introducing nonionic surfactant into the typically employed mixture of anionic surfactants, which drive the partitioning, is essential to increasing the ATPE system's resolution. A thorough analysis of the parameter space by experiments and modeling reveals the underlying interactions between SWCNTs, surfactants, and phase‐forming agents, which drive the partitioning. Based on new insight gained on this front, a separation mechanism is proposed. Notably, the developed method is highly robust, which is proven by isolating (6,4) SWCNTs from several raw SWCNT materials, including SWCNT waste generated over the years in the laboratory.